The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/medsci6020034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adipokines in Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IDD) is an important cause of low back pain. Recent evidence suggests that in addition to abnormal and excessive mechanical loading, inflammation may be a key driver for both IDD and low back pain. Obesity, a known mechanical risk factor of IDD, is now increasingly being recognized as a systemic inflammatory state with adipokines being postulated as likely inflammatory mediators. The aim of this review was to summarize the current literature regarding the inflammatory role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…Previous reports disclosed a lack of correlation between MRI/MCs scale and HDS [36,37]. Possible explanations for this finding are as follows: (1) sampling discrepancy, expected to be obvious in cases involving the lumbar spine because the protruded portion, rather than the whole disc, is removed; (2) use of qualitative and less complex grading criteria to obtain MRI/MCs scale [22]; (3) dehydration of the IVD detected on MRI (based on T2-weighted protocols) may simply represent the aging process rather than pathological IVD degeneration [38,39]; (4) fissures and cell clusters within the IVD seen under a microscope may not be detected with current MRI methodologies [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports disclosed a lack of correlation between MRI/MCs scale and HDS [36,37]. Possible explanations for this finding are as follows: (1) sampling discrepancy, expected to be obvious in cases involving the lumbar spine because the protruded portion, rather than the whole disc, is removed; (2) use of qualitative and less complex grading criteria to obtain MRI/MCs scale [22]; (3) dehydration of the IVD detected on MRI (based on T2-weighted protocols) may simply represent the aging process rather than pathological IVD degeneration [38,39]; (4) fissures and cell clusters within the IVD seen under a microscope may not be detected with current MRI methodologies [24].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for IVD degeneration include aging, genetic factors, nutrition, toxins, metabolic disorders, low-grade infection, neurogenic inflammation, autoimmune disease, and mechanical factors [3]. Obesity, a known mechanical risk factor, is recognized as a systemic inflammatory state mediated by adipokines [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is a fledging evidence base as to the role of leptin and the other adipokines in IVD degeneration. In a recent review, Sharma found only 15 in vitro studies investigating this relationship [61]. The author concluded that leptin can have significant effects on IVDs, but cautioned mechanistic and translational work is required to further understand this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out that higher BMI and low height are associated with the prevalence and severity of LBP [14]. Other than the increased axial load of the spine in case of high BMI, a high degree of adiposity was shown to increase the level of adipokines which may increase the rate of intervertebral degeneration causing LBP [15]. Furthermore, adipokines increased the risk of a mood disorder like depression which may affect the severity of chronic pain such as LBP [16].…”
Section: Discussionmentioning
confidence: 99%